Visual guidance during bicycle steering through narrow lanes: A study in children. (May 2015) - Vansteenkiste, Pieter; Cardon, Greet; Lenoir, Matthieu
Highlights: Higher cycling speed induces a more distant gaze behaviour in 8-year-old children. Wider cycling lanes induce more distant and task-irrelevant gaze in 8-year-old children. For a simple steering task, 8-year-olds and adults use similar visual-motor strategies. Abstract: Recently, Vansteenkiste et al. (2013) explored how visual behaviour guides bicycle steering when cycling at different speeds through 15 m long lanes of 10, 25 and 40 cm wide. Participants were found to shift their gaze direction towards the end of the lanes at higher speeds, towards the near pathway on narrow lanes and more towards irrelevant areas on wider lanes. To investigate to what extent young learner bicyclists adapt their visual behaviour in a similar way as adults, the experiment was repeated with seven eight-year-old children, and results were compared to the adult data. Children were found to cycle slower through narrow lanes than adults. However, with increasing lane width and cycling speed, children made the same shifts of visual gaze direction as the adults. These results suggest that for a simple precision steering task, children are able to adopt a similar visual-motor strategy as adults, provided that they cycle at their own pace.